Development of STEM professionals when integrating education research and physics public engagement into their careers - El-Adawy, Shams (Kansas State University, 2023)
To broaden participation in STEM (Science, Technology, Engineering, and Mathematics) education and continue building research capacity, this dissertation focuses on STEM professionals: those who take up education research later in their career and those who facilitate engagement in physics learning outside the formal classroom. Using agency, identity and motivation frameworks combined with qualitative research methodologies, we report on three projects that investigate how scientists integrate new research areas in their careers and engage with the public in order to gain a deeper understanding of their professional development needs. First, through a multiple case study analysis of three participants in a professional development program, we use Bandura’s theoretical framework on agency to investigate how program activities affect emerging STEM education researchers’ agency. Our analysis illustrates a mechanism by which professional development opportunities worked in favor of increasing self-efficacy and echoed more broadly into agency. Our study highlights the importance of agency when creating professional development activities to increase and sustain engagement in discipline-based education research (DBER) in different institutional contexts. Second, we use phenomenography grounded in Holland’s figured worlds to identify the spectrum of ways emerging STEM education researchers identify or imagine themselves in DBER. We characterize three ways they conceptualize education research: to improve teaching, to join a new field of research or to negotiate their position and identity in DBER vis-a-vis their home discipline. The nuanced experiences of these emerging STEM education researchers bring to the surface the challenges and opportunities of emerging STEM education researchers. Their experiences illustrate the need for a variety of professional development support including but not limited to nuanced and explicit discussions of the norms and culture of DBER within disciplinary science departments and discussions about DBER across STEM disciplines. Third, we use personas methodology and Ryan and Deci’s self-determination theory to articulate the motivation, challenges, and needs in public engagement of physicists with a range of different experiences. We discuss our personas refinement process, our set of personas and implications for the development of user-centered resources for the informal physics community. Our personas consist of the physicist who engages in informal physics for self-reflection, the physicist who wants to spark interest and understanding of physics and the physicist who wants to provide diverse role models to younger students and inspire them to pursue STEM careers. Needs covered a range of resources including science communication training, community building among informal physics practitioners and mechanisms to recognize, elevate and value informal physics. Using personas not only expands our understanding of motivations and needs of practitioners in physics public engagement, it brings user-centered design methodology to a new topical area of physics education research.
Keywords: Discipline-based education research; Physics education research; Professional development; Public engagement; Informal physics